Argentina : Second Review Under the Stand-By Arrangement and Requests for Modification and Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Argentina's Second Review Under the Stand-By Arrangement and Requests for Modification and Waiver of Performance Criteria. The economy is recovering rapidly, while inflation remains subdued. Strengthening consumer and business confidence and cautious monetary and fiscal policies have facilitated further reductions in interest rates, a stable peso, and further reserve accumulation. Buoyant tax revenues resulted in larger-than-programmed fiscal savings in 2003. Although high commodity prices and strengthening partner country demand are pushing export receipts to record levels, imports also continue to surge, driven by buoyant economic activity.